solve the equation
fast solve it
Attachments:
![](https://hi-static.z-dn.net/files/d5b/8ab5ef47c5f20b4a86c38bb88ea17e70.jpg)
Answers
Answered by
4
Answer:
x = -1
Step-by-step explanation:
HOPE YOU UNDERSTOOD THE SOLUTION
Answered by
0
Answer:
x - 3/6 - 6x + 1/3 = 1
so,[x -3 - 2(6x + 1)] /6= 1
x - 3 - 12x - 2 = 6× 1
-11x - 5 = 6
-11x = 11
hence, x = -1 would be the correct value of x.
Hope it helps you.
please mark my answer brainliest and please follow me.
Similar questions
Math,
2 months ago
Science,
2 months ago
Computer Science,
2 months ago
Chemistry,
1 year ago
Physics,
1 year ago